Hazard Observation Cards and Unsafe Actions Among Indonesian Vessel Crew - Faris Nofandi; Anisa Rahmawati; Sigit Purwanto (Media of Health Research, 2026)
This study examined the implementation of Hazard Observation Cards (HOC) aboard a commercial vessel operating in Indonesian waters. The results showed that 158 unsafe actions and unsafe conditions were identified through 87 completed HOC forms during a three-month observation period. This mixed-methods case study involved 15 crew members from March to May 2024. Data were collected through HOC documentation, field observations, interviews, and safety records. Quantitative analysis used descriptive statistics and Cochran-Armitage trend tests, while qualitative data were analyzed thematically. Unsafe conditions (57.0%) were more frequent than unsafe actions (43.0%). Violations decreased significantly from 113 in March to 82 in May (Z = -2.84; p = 0.004). The most common unsafe practices involved the failure to use personal protective equipment and housekeeping deficiencies. Safe practices referred to compliance with maritime safety procedures, including the use of PPE, adherence to procedures, and hazard control measures. Interviews indicated that visible management responses increased crew safety awareness and participation. The findings suggest that HOC can function as a feasible participatory safety monitoring tool for small-crew maritime operations and may contribute to improved occupational safety performance.